2020
DOI: 10.1002/dc.24655
|View full text |Cite
|
Sign up to set email alerts
|

Concordance ofHPV, conventional smear, colposcopy, and conization results in cervical dysplasia

Abstract: Background Cervical cancer screening algorithms are increasingly focused on Human Papillomavirus (HPV)‐based screening while the accuracy of using abnormal cytological findings to detect dysplastic lesions still remains important. This retrospective study correlated the results of conventional cervical cytology, colposcopy guided biopsy, and cold knife conization (CKC) procedures performed in a tertiary center. Materials and Methods Data from 9399 patients who underwent screening with conventional cervical cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…При расчете показателей эффективности цитологического метода Se для традиционной цитологии составила 75,9%, Sp -82,4%. Наши данные сопоставимы с данными других исследователей, согласно которым Se для традиционного метода составляет диапазон от 42,2 до 87,2%, а Sp -от 69,2 до 99,4% [13][14][15][16][17] [19][20][21]. Данный показатель по результатам нашего исследования составляет 80% (для традиционной цитологии -80,9%, для метода жидкостной цитологии -77,5%).…”
Section: Discussionunclassified
“…При расчете показателей эффективности цитологического метода Se для традиционной цитологии составила 75,9%, Sp -82,4%. Наши данные сопоставимы с данными других исследователей, согласно которым Se для традиционного метода составляет диапазон от 42,2 до 87,2%, а Sp -от 69,2 до 99,4% [13][14][15][16][17] [19][20][21]. Данный показатель по результатам нашего исследования составляет 80% (для традиционной цитологии -80,9%, для метода жидкостной цитологии -77,5%).…”
Section: Discussionunclassified
“…Other studies showed that conventional cytology had an overall sensitivity of 50 to 75% for detecting low-grade lesions and of 55 to 90% for high-grade lesions (CIN II/III). 8,10,11 Considering women whose cytological results have highgrade characteristics with indications to proceed directly to colposcopy and possible biopsy, 54.4% underwent a second cytological test, not following the current guidelines. Of this group, 29.1% had some type of neoplasm in a later biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that conventional cytology had an overall sensitivity of 50 to 75% for detecting low-grade lesions and of 55 to 90% for high-grade lesions (CIN II/III). 8 10 11 …”
Section: Discussionmentioning
confidence: 99%
“…Mustard yellow areas with distinct borders suggest more severe disease [ 11 ]. Colposcopy assessment more often overestimates the severity of lesions; however, given the minor side effects of biopsy and the substantial morbidity that may follow a false-negative, and detection of HPV may prevent unnecessary surgical procedures, especially with ASCUS [ 12 ]. Because the colposcopic diagnosis of pre-invasive cervical carcinoma has a sensitivity ranging from 79% to 82% and specificity ranging from 73% to 87% [ 13 ], keeping colposcopy in the gynecologist’s toolbox is advisable, and new colposcopy approaches are being developed [ 14 ].…”
Section: Discussionmentioning
confidence: 99%